2016
DOI: 10.1016/j.celrep.2016.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Modeling of Reprogramming to Induced Pluripotent Stem Cells

Abstract: Reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) is typically an inefficient and asynchronous process. A variety of technological efforts have been made to accelerate and/or synchronize this process. In order to define a unified framework to study and compare the dynamics of reprogramming under different conditions, we developed an in silico analysis platform based on mathematical modeling. Our approach takes into account the variability in experimental results stemming from probabilist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…By investigating OSKM binding at 48 h of reprogramming, previous studies have begun to elucidate the patterns and regulatory roles of OSKM in early reprogramming in the human and mouse systems [810]. Reprogramming typically is an inefficient process where only few cells in the culture dish induce the pluripotency program, yielding a highly heterogeneous cell population at the end of the process [11]. In previous studies, Koche et al demonstrated that within the first few days of iPS reprogramming, dividing and nondividing cells exhibited highly similar transcriptional profiles [12].…”
Section: Introductionmentioning
confidence: 99%
“…By investigating OSKM binding at 48 h of reprogramming, previous studies have begun to elucidate the patterns and regulatory roles of OSKM in early reprogramming in the human and mouse systems [810]. Reprogramming typically is an inefficient process where only few cells in the culture dish induce the pluripotency program, yielding a highly heterogeneous cell population at the end of the process [11]. In previous studies, Koche et al demonstrated that within the first few days of iPS reprogramming, dividing and nondividing cells exhibited highly similar transcriptional profiles [12].…”
Section: Introductionmentioning
confidence: 99%
“…These reprogramming protocols make specific predictions concerning reprogramming dynamics which are broadly in line with experimental findings. Another reprogramming model using a two-type continuous-time Markov process with a constant reprogramming rate has revealed two different modes of cellular reprogramming dynamics: TF expression alone leads to heterogeneous reprogramming while TFs plus certain other factors homogenise the dynamics [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CD2/CD58 axis promotes cell-to-cell adhesion and immunological synapse formation, providing an important co-stimulatory signal on effectors (Siliciano et al, 1985;Selvaraj et al, 1987;Browne et al, 1990) (Leitner et al, 2015). More recently, CD2 has been shown to play a role in costimulation of adaptive NK cells (Rölle et al, 2003;Liu et al, 2016). Furthermore, inhibition of CD58/LFA-3 expression by the viral protein UL148 has revealed that the CD2/CD58 axis is also needed for the recognition of HCMV-infected cells by NK cells and HCMV-specific CTLs .…”
Section: Nk Cells and Hcmv: A Balance Of Opposing Forcesmentioning
confidence: 99%